VD_FINDINFO HC / 2011 / 586 vom 4. Oktober 2011 - VD Tribunal cantonal (2011)
PROTECTION DE L'ENFANT, MESURE PROVISIONNELLE, PREUVE FACILITÉE, DROIT DE GARDE | 307 al. 3 CC, 261 al. 1 CPC (CH), 308 al. 1 let. b CPC (CH), 310 CPC (CH)